2023
DOI: 10.3389/fvets.2023.1117829
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in equine platelet lysate and related blood products

Abstract: In equine medicine, the use of regenerative therapeutics has gained growing attention, but is still a new and complex field with room for improvement. Platelet lysate (PL) can be used as therapeutic agent but is also a promising supplement for the culture of multipotent mesenchymal stromal cells. To enable a targeted use of PL both in clinic and laboratory, it is crucial to learn more details on its effective ingredients. While so far, mainly growth factor components have been analyzed in platelet-based produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Equine PL contains a naturally composed mix of cytokines, and therefore might mimic inflammation to an extent that beneficially impacts on MSC. However, donor effects on PL composition should be considered: in a previous study, we found that cytokine levels in PL were subject to high individual variation ( 4 ). Particularly horses with increased alkaline phosphatase, creatinine and lactate dehydrogenase values also had an increased concentration of IFN-γ, TNF-α, IL-4, IL-6, IL-10 and IL-1β in their blood products including PL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equine PL contains a naturally composed mix of cytokines, and therefore might mimic inflammation to an extent that beneficially impacts on MSC. However, donor effects on PL composition should be considered: in a previous study, we found that cytokine levels in PL were subject to high individual variation ( 4 ). Particularly horses with increased alkaline phosphatase, creatinine and lactate dehydrogenase values also had an increased concentration of IFN-γ, TNF-α, IL-4, IL-6, IL-10 and IL-1β in their blood products including PL.…”
Section: Discussionmentioning
confidence: 99%
“…PL contains a diversity of nutrients and growth factors such as TGF-β and PDGF ( 1 , 3 ). However, even while using a leukocyte-poor platelet concentrate for PL production ( 1 ), the resulting PL also contains a variety of cytokines including IFN-γ, IL-10, IL-1β, IL-4, IL-6 and TNF-α ( 4 ). Cytokines are a group of peptides that regulate the proliferation and differentiation of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the aforementioned cytokines, adipocytes also produce other molecules such as leptin (LEP) and C-reactive protein (CRP), which together with infammation are responsible for inhibiting the expression of genes regulating the metabolism of fatty acids and glucose and decreased secretion of certain antihyperglycemic adipokines [9][10][11][12]. In addition, to the abundant proinfammatory adipokines described previously, AT also secretes some anti-infammatory factors, as for instance IL-4 or IL-10 [13,14]. Although exerting a pleiotropy of biological activities, interleukins 4 and 10 are essentially recognized for their immunosuppressive efects mediated through proinfammatory cytokine expression lowering and inducing type-switching of M1 to M2 macrophages under acute or prolonged infammatory states [15,16].…”
Section: Introductionmentioning
confidence: 99%